Nuclear factor I X is a recurrent target for HPV16 insertions in anal carcinomas. Issue 12 (27th September 2018) - Jeannot, Emmanuelle; Harlé, Alexandre; Holmes, Allyson; Sastre‐Garau, Xavier
Abstract: Anal carcinomas (AC) are associated with human papillomavirus (HPV) DNA sequences, but little is known about the physical state of the viral genome in carcinoma cells. To define the integration status and gene(s) targeted by viral insertions in AC, tumor DNAs extracted from 35 tumor specimen samples in patients with HPV16‐associated invasive carcinoma were analyzed using the detection of integrated papillomavirus sequences‐PCR approach. The genomic status at integration sites was assessed using comparative genomic hybridization‐array assay and gene expression using reverse transcription quantitative PCR (RT‐qPCR). HPV16 DNA was found integrated in 25/35 (71%) cases and the integration locus could be determined at the molecular level in 19 cases (29 total integration loci). HPV DNA was inserted on different chromosomes, but 5 cases harbored viral sequences at 19p13.2, within the nuclear factor I X ( NFIX ) locus. Viral DNA mapped between the most distal and the two proximal alternatively expressed exons of this gene in three cases (CA21, CA04, and CA35) and upstream of this gene (663 kb and 2.3 Mb) in the others. CGH arrays showed genomic gains/amplifications at the NFIX region, associated with HPV within the gene and RT‐qPCR, revealed NFIX mRNA overexpression. Other genes targeted by integration were IL20RB, RPS6KA2, MSRA1, PIP5K1B, SLX4IP, CECR1, BCAR3, ATF6, CSNK1G1, APBA2, AGK, ILF3, PVT1, TRMT1, RAD51B, FASN, CCDC57, DSG3, and ZNF563. We identified recurrent targeting of NFIX by HPV16 insertion in anal carcinomas, supporting a role for this gene in oncogenesis, as reported for non‐HPV tumors.